A study on partial and full replacement of fine aggregate in high-performance concrete with granulated blast furnace slag. Issue 1 (November 2020) - Srinivas, Dodda; Chitirala, Hardik; Srinivasarao, C H; Adak, Dibyendu
Abstract: The influence of the partial / full replacement of fine aggregates with granulated blast furnace slag (GBS) and its effect on mechanical strength and durability properties (acid attack) of high-performance concrete of grade (M60) had been studied in the present work. The high-performance concrete mix had been designed in such a way that one group with natural sand and another with manufactured sand (Quarry dust). Each group of concrete mix with natural and manufactured sand consisted of five sub-groups, having 0%, 30%, 50%, 80% and 100% of GBS content. Other pozzolanic materials such as fly ash and silica fume were also employed to replace ordinary Portland cement (OPC) at 20% and 8% respectively, with a constant w/c ratio of 0.32 for the desired slump of 100 mm. According to the results, all the replacement levels of fine aggregate by GBS proved to enhance the mechanical and durability performance of concrete. It is concluded that the high-performance concrete can be produced by utilizing 100% GBS as fine aggregate, with improved mechanical and durability performance.